Income Distribution, Informal Safety Nets, and Social Expenditures in Uganda - McDonald, Calvin; Schiller, Christian; Ueda, Kenichi (Washington, D.C. : International Monetary Fund, 1999)
Inequality in Uganda rose during 1989-95, although this rise moderated in 1993-95. In 1993-95, real food consumption became more equal. Regional and urban-rural disparities in income and variations in income accruing to individuals with different educational levels principally explain 'between group inequality.' While informal safety nets appear to work for Ugandan middle-class families, a lack of mutual insurance among poor production workers and farmers accentuates the inequality trends. An expansion of formal safety nets would help this segment of the population. The intrasectoral allocation and benefit incidence of expenditures on education and health can be improved to reduce inequality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet